2020
DOI: 10.3389/fvets.2020.00102
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonography-Guided Perineural Injection of the Ramus ventralis of the 7 and 8th Cervical Nerves in Horses: A Cadaveric Descriptive Pilot Study

Abstract: To describe the feasibility and dye diffusion of selective perineural injection of the 7 and 8th cervical nerve (C7 and C8) ramus ventralis under ultrasonographic guidance in horses. Study design: Prospective experimental pilot cadaver study. Animals: Four equine cadavers of similar body weight (420-480 kg) and neck conformation. Methods: Five C7 and five C8 rami were perineurally injected with a dye solution. Anatomic dissections including vertebral canal opening were conducted to confirm nerve dye staining a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(24 citation statements)
references
References 27 publications
3
21
0
Order By: Relevance
“…Similar studies in which ultrasonographicguided approaches to intra-articular injection of the cervical APJ have been described have provided evidence of comparable success rates of 72% and 89%. 10,11 Touzot-Jourde et al 12 concluded that perineural injection of the ventral ramus was feasible and the technique described by the authors. The study shares similarities with regard to the general technique and landmarks for injection.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Similar studies in which ultrasonographicguided approaches to intra-articular injection of the cervical APJ have been described have provided evidence of comparable success rates of 72% and 89%. 10,11 Touzot-Jourde et al 12 concluded that perineural injection of the ventral ramus was feasible and the technique described by the authors. The study shares similarities with regard to the general technique and landmarks for injection.…”
Section: Discussionmentioning
confidence: 99%
“…4 A cadaveric pilot study has recently been published in which researchers demonstrated that ultrasonographic-guided cervical perineural injection is feasible in horses. 12 In this study, 12 a micro convex probe was used in a longitudinal plane, and 7 to 14 mL of methylene blue was injected into 10 sites. There were issues relating to dye diffusion, which the authors found in their pilot study in which methylene blue was injected.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This study highlighted the feasibility of perineural injection techniques as a potential treatment option for cervical radiculopathy in the horse. Touzot-Jourde et al (2020) published a pilot cadaver study of four horses in which they described an US-guided perineural injection technique for the ramus ventralis of the 7th and 8th cervical nerves in the horse [50]. A total of 10 injections were performed, and all were deemed accurate using a large volume of injection (7 ml or 14 ml), as demonstrated by evidence of dye staining a portion (2/10) or the entire (8/10) cross section of the ramus ventralis nerve trunks [50].…”
Section: Cervical Nerve Rootsmentioning
confidence: 99%
“…(2020) published a pilot cadaver study of four horses in which they described an US-guided perineural injection technique for the ramus ventralis of the 7th and 8th cervical nerves in the horse [ 50 ]. A total of 10 injections were performed, and all were deemed accurate using a large volume of injection (7 m l or 14 m l ), as demonstrated by evidence of dye staining a portion (2/10) or the entire (8/10) cross section of the ramus ventralis nerve trunks [ 50 ]. Some diffusion was noted in the epidural space in 5/10 injections [ 50 ].…”
Section: Atlanto-axial Spacementioning
confidence: 99%